Hybrid Proton Exchange Membrane
A hybrid proton exchange membrane with thiol groups in the cathode layer addresses membrane degradation in fuel cells, improving performance and lifespan by reacting with hydrogen peroxide and maintaining conductivity.
Patent Information
- Application Number
- JP2021008716
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-23
- Filing Date
- 2021-01-22
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2041-01-22
AI Technical Summary
Fuel cell membranes deteriorate due to high or low temperatures, high humidity, and hydrogen peroxide, leading to reduced performance and lifespan.
A hybrid proton exchange membrane composed of organic and inorganic components, featuring thiol groups (-SH) in the cathode layer, which reacts with hydrogen peroxide to prevent degradation and maintain conductivity.
The membrane enhances fuel cell performance and extends its lifetime by self-regenerating and maintaining conductivity under adverse conditions.
Smart Images

Figure 0007617750000006 
Figure 0007617750000007 
Figure 0007617750000008
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of fuel cells, and in particular to the field of proton exchange membranes used in these cells. [Background technology]
[0002] Proton exchange membranes or polymer electrolyte membranes (PEMs) are semipermeable membranes that are impermeable to gases such as O2 or H2, but allow proton conductivity, i.e., protons pass through the membrane even though the gas is stopped. PEMs are typically made from pure polymer membranes or composite membranes with a polymer base.
[0003] Fuel cell membranes based on sulfonated copolymers of tetrafluoroethylene and perfluoro(alkyl vinyl ether) are also known. For example, one of the materials most widely used by manufacturers of proton exchange membranes is Nafion®, a sulfonated fluorinated copolymer manufactured by DuPont.
[0004] Canadian Patent No. 2950775 describes electrospun fiber webs for reinforcing fuel cell membranes.
[0005] US Patent Application Publication No. 2007 / 0213494 describes silica-based organic-inorganic (hybrid) polymers and their use as proton exchange materials.
[0006] However, operation of fuel cells causes degradation of the membrane due to high or very low temperatures, high relative humidity (close to 90%), and the production of hydrogen peroxide (H2O2), which degrades the materials. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Canadian Patent No. 2950775 [Patent Document 2] US Patent Application Publication No. 2007 / 0213494 Summary of the Invention [Problem to be solved by the invention]
[0008] Therefore, there is a need for improved membranes to be available that are more resistant to these inhibitory effects and exhibit longer life spans. [Means for solving the problem]
[0009] The invention therefore proposes a membrane based on a hybrid material, based on organic and inorganic components, which is capable of reacting in particular with hydrogen peroxide, such that said membrane retains good mechanical and electrical conductivity properties.
[0010] According to a first object, the present invention provides a proton exchange membrane for a fuel cell, said membrane comprising an anode face on the anode side and a cathode face on the cathode side, said membrane comprising two layers: a self-regenerating conductive cathode layer comprising a polymer (iii) having at least one SOH group, providing a cathode surface; and a conductive anode layer comprising a polymer (iii') having at least one SO3H group, which provides an anode surface; Including, The polymers (iii) and (iii') may be the same or different, The membrane is characterized in that the cathode layer comprises a polymer (i) carrying at least one thiol group (-SH).
[0011] According to the invention, the membrane comprises SH groups present at the cathode, ie within the cathode layer of the membrane.
[0012] SH groups may also be present within the cathode catalyst layer of a fuel cell.
[0013] Thus, a cell comprising a membrane according to the invention advantageously comprises a region functionalised with SH groups extending from the cathode layer of the membrane to the cathode catalyst layer present on its surface.
[0014] According to one embodiment, the -SH groups may be uniformly distributed within the cathode layer, and optionally within the cathode catalyst layer.
[0015] Alternatively, the -SH groups may be distributed according to a concentration gradient of -SH groups that increases towards the cathode surface, the gradient exhibiting an increasing SH group concentration from the inner surface of the cathode layer associated with the anode layer towards its outer surface, which provides the interface with the cathode catalyst layer.
[0016] By the inner surface of the membrane is meant the interface between the cathode layer and the anode layer.
[0017] By exterior surface of the membrane is meant the cathode and anode sides of the membrane which provide the interfaces with the cathode and anode catalyst layers, respectively.
[0018] The proton exchange membrane according to the invention is self-regenerating, in which it uses harmful hydrogen peroxide, which is produced during the operation of the cell and which degrades the membrane. The SH groups present in the cathode layer (and possibly in the cathode catalyst layer) react to consume the hydrogen peroxide, thus preventing its harmful accumulation. In addition, this reaction produces SO3H groups, which maintain and even regenerate and improve electrical conductivity.
[0019] Thus, the membrane according to the present invention can greatly improve the performance and life of fuel cells.
[0020] According to one embodiment, said layer consists of hybrid fibres, for example obtained by electrospinning.
[0021] According to one embodiment, the membrane according to the invention is called hybrid since it comprises an organic component and an inorganic component (also called mineral here).
[0022] Generally, the organic component provides the electrical conductivity while the inorganic component provides the web.
[0023] Typically, the web is a silicate inorganic web, for example of Nafion® type, or sulfonated polyether. Thus, according to one embodiment, the cathode layer and / or the anode layer respectively comprise an inorganic polymer (ii) and / or (ii'), said polymers (ii) and (ii') being the same or different. Preferably, the polymers (ii) and (ii') are derivatives of silicon.
[0024] The membrane according to the invention thus combines the ability to mimic the structural phase separation observed in Nafion® membranes with oriented ionic nanochannels through which protons can easily diffuse.
[0025] Furthermore, the membrane composition exhibits a favorable hydrophilic / hydrophobic ratio that improves the proton diffusion and wetting properties of the membrane.
[0026] The morphology and composition of the film provide good mechanical properties over a wide range of temperatures, which may range from negative temperatures to approximately 120°C.
[0027] According to one embodiment, the membrane according to the invention comprises: - an organic polymer selected from polymers (i) containing SH groups and / or polymers (iii) and (iii') containing SOH groups, - inorganic polymers (ii) and (ii') derived from silicon It consists of a mixture of
[0028] The silicon-derived polymer forms a random three-dimensional continuous porous web within which the organic components are embedded.
[0029] As regards the cathode layer, the organic polymer is in particular composed of a polymer (i) having SH groups and a polymer (iii) having SO3H groups.
[0030] Within the cathode layer, the ratio of the SO3H group concentration to the SH group concentration is generally between 0.5 and 4, preferably between 1 and 4.
[0031] As regards the anode layer, the organic polymer is in particular composed of a polymer (iii') carrying SO3H groups.
[0032] As regards the cathode and anode layers, the inorganic polymer is in particular composed of the silicon-derived polymers (ii) and (ii'), respectively.
[0033] According to one embodiment, in the cathode layer, the polymers (ii), (iii) and (i) are present in a ratio of 1:2:1; In the anode layer, the polymers (ii') and (iii') are in a ratio of 1:2.
[0034] The thiol (-SH) group-bearing polymer (i) may in particular be (3-mercaptopropyl)trimethoxysilane (MPTMS) of the following formula: [ka]
[0035] Polymers (ii) and / or (ii') include silicon derivatives such as tetraethyl orthosilicate (TEOS) or tetramethyl orthosilicate (TMOS) of the following formula:
[0036] [ka]
[0037] The inorganic polymers (ii) and / or (ii') can also be Nafion® type derivatives or sulfonated polyethers.
[0038] The organic polymer provides the backbone of the membrane.
[0039] Polymers (iii) and / or (iii') carrying SO3H groups include in particular CSPTC (2-(4-chlorosulfonylphenyl)ethyltrichlorosilane) of the following formula:
[0040] [ka]
[0041] According to one alternative embodiment using a mixture of polymers as discussed above, the organic and inorganic components are co-condensed, i.e., the silicon polymer forms a web onto which the organic polymer is grafted.
[0042] According to this embodiment, the polymers (i), (ii) and (iii) on the one hand and the polymers (ii') and (iii') on the other hand are copolymerized in such a way as to constitute an organic-mineral copolymer, i.e. a copolymer comprising simultaneously an organic component and a mineral component.
[0043] Thus, the silica derivatives can be functionalized with SH and / or WO3H groups depending on the cathode or anode layer.
[0044] The identical or different polymers (i), (ii), (ii'), (iii), (iii') may then each be selected from silicon-derived (co)polymers carrying SH and / or SO3H groups.
[0045] In any of the above embodiments, the polymer in the mixture or copolymerized state comprises simultaneously a mineral component (polymer (ii) or (ii') derived from silicon) to enable stiffness of the web, and an organic component (polymer (i), (iii) or (iii')) whose SH and / or SO3H groups provide mobile protons (possibly after hydrolysis of the SH groups as in the case of polymer (i)).
[0046] Typically, the anode layer and the cathode layer may further comprise one or more non-conductive (co)polymers to ensure the mechanical properties of the membrane. These polymers are known and are commonly used in membranes for this purpose. For example, non-conductive polymers include poly(vinylidene fluoride) (PVDF), poly(co-hexafluoropropylene) (HFP), mixtures thereof and / or copolymers thereof corresponding to the following formula: poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP).
[0047] [ka]
[0048] The cathode and anode layers of the membranes according to the invention may further comprise one or more organic or inorganic additives, which may be the same or different from one layer to the other.
[0049] Additives conventionally used in proton conductor membranes are also contemplated here, including in particular PEO (polyethylene glycol) and OFP (2,2,3,3,4,4,5,5-octafluoro-1-pentanol (OFP)), respectively of the following formula:
[0050] [ka]
[0051] PEO improves the electrical conductivity and mobility of the PVDF-HPF chains, while OFP improves the affinity between PVDF-HFP (thanks to the carbon chains carrying fluorine atoms) and the inorganic components (due to the presence of hydroxyl groups).
[0052] The total thickness of the membrane according to the invention is generally between 5 and 150 μm, typically between 15 and 40 μm.
[0053] According to one embodiment, the cathode layer is thinner than the anode layer. Typically, said cathode layer has a thickness between 5 and 10 μm.
[0054] According to one embodiment, the anode layer and / or the cathode layer are composed of polymeric fibers of the above-mentioned blends or copolymerized polymers.
[0055] These fibers are interwoven in a random manner to produce a porous three-dimensional web.
[0056] Typically, these fibres have an average diameter between 100 nm and 10 μm, which can be adapted in particular depending on the nozzle diameter of the electrospinning device used during their production.
[0057] According to another object, the present invention also relates to a fuel cell comprising a bilayer membrane according to the invention.
[0058] In such a cell, the membrane according to the invention is coated with a cathode catalyst layer on the outer surface of the cathode layer, and with an anode catalyst layer on the outer surface of the anode layer.
[0059] According to one embodiment, the cathode catalyst layer comprises polymers (i) and (iii) and the anode catalyst layer comprises polymer (iii'), said polymers (i), (iii) and (iii') being as defined above.
[0060] A diagram illustrating the construction of a battery according to the present invention is shown in FIG.
[0061] As illustrated in Figure 2, The fuel cell consists of an anode (5') and a cathode (5) separated by a proton exchange membrane (3), said membrane (3) comprising a cathode layer (1) on the cathode side and an anode layer (2) on the anode side.
[0062] The cathode layer (1) typically has a thickness e1 between 3 and 15 μm, in particular between 5 and 10 μm, preferably between 5 and 7 μm. The anode layer (2) typically has a thickness e2 between 5 and 40 μm, in particular between 10 and 30 μm, preferably between 10 and 20 μm.
[0063] On the cathode side outer surface of the membrane (3), the cathode layer (1) is coated with a cathode catalyst layer (4).
[0064] On the anode-side outer surface of the membrane (3), the anode layer (2) is coated with an anode catalyst layer (4').
[0065] The cathode catalyst layer (4) and the anode catalyst layer (4') comprise a proton conductor (ionomer) (11) and (21), respectively, within which are distributed catalytic particles (12) and (22), respectively. Conventionally, these catalytic particles consist of platinum (Pt) particles on a carbon support.
[0066] The cathode layer (1) contains, in particular, SH and SO3H groups, which are also present inside the cathode catalyst layer (4), thus defining an area (1') functionalized by SH groups, consisting of the cathode layer (1) and the cathode catalyst layer (4).
[0067] The anode layer (2) contains SO3H groups, which are also present within the anode catalyst layer (4').
[0068] According to another object, the present invention also relates to a method for preparing a membrane according to the invention, which method comprises the following steps: - formation of fibres constituting the cathode layer by electrospinning from a solution comprising at least one polymer (i) carrying thiol groups (-SH) and at least one polymer (iii) carrying SO3H groups, - the formation of fibres constituting the anode layer by electrospinning from a solution comprising at least one polymer (iii') carrying SO3H groups; - forming an anode layer and a cathode layer, respectively, from the obtained fibers; - attaching said cathode layer onto said anode layer; Includes.
[0069] According to one embodiment, the solution is a sol-gel solution.
[0070] The method according to the invention combines sol-gel chemistry and electrospinning techniques, making it possible to obtain membranes with anisotropic mechanical properties and a proton conductivity at high temperature and 90% relative humidity comparable to that of Nafion® membranes.
[0071] The morphology of the electrospun membranes according to the present invention can be tuned by the sol-gel synthesis (e.g. with or without additives) and / or the electrospinning process parameters, such as the relative humidity, the applied electric field, the temperature, the rotation speed of the electrodes.
[0072] Electrospinning, or electrostatic spinning, is a fiber manufacturing method that uses electrical forces to draw threads of a set polymer. The technique is based on applying high enough pressure to a microdroplet of liquid polymer (in solution or melt state): the liquid is charged, and then the electrostatic repulsion opposes the surface voltage, thereby stretching the droplet to a critical point (the jetting point or "Taylor cone"), where a stream of liquid ejects from the surface. If the molecular cohesion of the liquid is high enough, the stream will not break and a liquid-filled jet will form. The jet then lengthens by a process driven by electrostatic repulsion until it finally ejects onto a collector ground. The stretching and thinning of the fiber results in the formation of uniform "electrospun" fibers with nanometer diameters.
[0073] The sol-gel process consists of producing an oxide web (network) from molecular precursors, generally metal alkoxides, by inorganic polymerization in solution. This polymerization occurs by hydrolysis and condensation. The hydrolysis step is generally carried out with a catalyst, which can be an acid or a base. It consists of a reaction between water and the precursor to produce reactive groups of hydroxy type, in the form of a solution called a sol. Condensation consists of gelation and the conversion of the hydroxy groups, which leads to the formation of a gel, whose viscosity increases over time and forms an inorganic polymer web. The "gel" phase in the sol-gel process is defined and characterized by a solid three-dimensional "skeleton" contained in a liquid phase. The solid phase is typically a condensed polymer sol, in which the particles begin to intertwine and form a three-dimensional web.
[0074] According to one embodiment, said solution is prepared by mixing the (co)polymer in an organic solvent in the presence of an inorganic sol-gel precursor.
[0075] The resulting sol-gel can be called a "sol-gel hybrid" in that organic molecules are added during synthesis and are preserved in the final material.
[0076] Typically, the mineral precursor (inorganic precursor) is silica functionalized with sulfonic acid (SO3H-SiO2).
[0077] Generally, the concentration of said (co)polymer in the solution is between 5 and 20% by weight.
[0078] The sol-gel synthesis can advantageously be carried out at room temperature. Routinely, the temperature, pH, nature of the precursors and solvent, and concentrations of the reactants may be adjusted.
[0079] Thus, the membrane obtainable by the method according to the invention comprises a random three-dimensional continuous porous web of electrospun hybrid (co)polymer fibers. [Brief description of the drawings]
[0080] [Figure 1] FIG. 1 is an illustration of an electrospinning method for synthesizing the fibers that make up the membrane according to the present invention. [Diagram 2] FIG. 1 shows the structure of a fuel cell including a membrane according to the invention. [Diagram 3] FIG. 1 shows an EDX analysis showing the distribution of the various elements in the fiber: oxygen (a), silicon (b), sulfur (c), fluorine (d). [Figure 4] FIG. 13 is a graph illustrating the change in proton conductivity as a function of relative humidity and the presence or absence of self-regenerating SH groups for electrospun hybrid membranes containing polymers (ii') and (iii') in a 1:2 ratio (TEOS:CSPTC (1:2)) or polymers (i), (ii), and (iii) in a (ii):(iii):(i)=1:2:1 ratio (TEOS:CSPTC:MPTMS (1:2:1)). [Diagram 5]FIG. 1 is a graph showing the change in proton conductivity as a function of relative humidity and as a function of the presence or absence of self-regenerating SH groups for electrospun hybrid membranes after accelerated aging tests, for membranes containing polymers (ii') and (iii') in a 1:2 ratio (TEOS:CSPTC (1:2)) or polymers (i), (ii), and (iii) in a ratio (ii):(iii):(i)) = 1:2:1 (TEOS:CSPTC:MPTMS (1:2:1)). [Figure 6] Photographs of the two surfaces of the bilayer membrane: the left photograph represents the anodic side (conductive anode layer) and the right image represents the cathodic side (self-regenerating cathode layer). [Figure 7] Scanning electron microscope (SEM) images showing the structure of the conductive anode layer (a), the self-regenerating cathode layer (b), and a cross-section of the bilayer (c). [Figure 8] 1 is a graph illustrating the variation in conductivity as a function of relative humidity for an anode layer (a) and a cathode layer (b). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES
[0081] 1. Synthesis and Characterization Cathode layer solution A sol-gel solution was prepared by pre-dissolving the non-conductive polymer (PVDF-HFP) in dimethylformamide (DMF) (600 mg PVDF-HFP in 700 mL DMF), and then additives (PEO: polyethylene glycol, and OFP: 2,2,3,3,4,4,5,5-octafluoro-1-pentanol) were added (340 mg PEO and 60 mg OFP). Then, the silicon precursors (TEOS (tetraethyl orthosilicate, 310 mg), CSPTC (2-(4-chlorosulfonylphenyl)ethyltrichlorosilane, 2.04 g, from a 50 wt.% solution in dichloromethane), and MPTMS ((3-mercaptopropyl)trimethoxysilane, 310 mg) were added according to the various molar ratios tested, with the most reactive CSPTC being added last. The solution was aged under stirring at 70 °C for 3 h in order to prehydrolyze the silicon precursors. A homogeneous solution V2 was obtained, containing SH and -SO3H groups and exhibiting a TEOS / CSPTC / MPTMS ratio of 1:2:1. Solutions with ratios of 1:2:2 and 1:1:1 were also prepared following this procedure.
[0082] Anode layer solution To obtain solution V1 (containing -SO3H groups), the procedure was carried out as described above from the precursor mixture, excluding MPTMS.
[0083] Electrospinning Next, fibers were prepared by electrospinning the resulting solutions of V1 and V2, respectively.
[0084] The electrospinning apparatus used (as illustrated in FIG. 1) included a syringe and needle (ID = 0.75 mm), a ground electrode, and a commercially available high-voltage power supply unit (ES1a, Electrospinz). The needle was connected to the high-voltage power supply unit, which was capable of generating a voltage of up to 40 kV of positive continuous current.
[0085] Two syringes were prepared, each containing a volume of solution V1 or solution V2. For solution V1, 0.15 mL and for solution V2, 0.075 mmL were used to obtain a total thickness of 20 microns. Each solution, V1 and V2, was electrospun at 26 kV with a flow rate depending on the ambient humidity. Typically, the relative humidity should be less than 60% and the flow rate should be around 0.025 mL.min -1 The steel needle was connected to the electrode of a high voltage power supply unit, and a piece of aluminum foil connected to ground was placed 15 cm from the tip of the needle to collect the various layers. To generate the second layer of the film, the first syringe was replaced by the second syringe.
[0086] A white flexible membrane was obtained. Finally, the proton exchange membrane was dried in air at 70°C for 24 hours. After drying, the EHS separator was carefully peeled off from the aluminum foil. The membrane thickness can be between 15 and 40 microns depending on the volume injected into the electric field.
[0087] The two layers thus obtained are represented in FIG.
[0088] Analysis of the membrane The structures were examined by scanning electron microscopy, as depicted in FIG.
[0089] Scanning electron spectroscopy images of the surface and cross-section of the electrospun proton exchange membrane show intertwined fibers (D = 200 nm) organized in a three-dimensional space, defining a 85.4% open porosity network. The membrane thickness was measured to be about 20 μm. EDX analysis of the fibers (Figure 3) shows a uniform surface distribution of the elements O, F, S, and Si, without any phase separation at the micrometer level.
[0090] 2.Characteristics Water retention calculations show that the TEOS:CSPTC:MPTMS (1:2:1) cathode layer is significantly less hydrophilic than the corresponding TEOS:CSPTC (1:2) anode layer (141.9% water vs. 69.6% water).
[0091] The self-regenerating properties of membranes containing a cathode layer exhibiting -SH groups were analyzed.
[0092] The change in proton conductivity as a function of humidity, as shown in Figure 4, indicates that the addition of self-regenerable reactive functional groups only slightly affects the conductivity values of the conventional membranes. However, the membranes containing -SH groups exhibit better resistance to oxidation, especially in the presence of H2O2, as shown in Figure 5, which shows the retention of conductivity after accelerated aging tests.
[0093] The effect of the ratio of -SO3H / SH groups on the physicochemical properties of the membranes was studied for different compositions: For the anode layer, the following TEOS:CSPTC ratios were tested: 1:2, 1:3, 1:1, and 2:1 For the cathode layer, the following TEOS:CSPTC:MPTMS ratios were tested: 1:2:1, 1:2:2, and 1:1:1.
[0094] The effect on conductivity is shown in Figure 8, which represents the change in conductivity as a function of humidity level for different compositions of hybrid films. The left panel represents the change in conductivity as a function of TEOS / CSPTC ratio, and the right panel represents the change in conductivity as a function of TEOS / CSPTC / MPTMS amount. These tests show that values of 1:2 TEOS:CSPTC and 1:2:1 TEOS:CSPTC:MPTMS give the best results in terms of conductivity at 80°C. [Explanation of symbols]
[0095] 1. Cathode layer Regions functionalized with 1'···SH groups 2. Anode layer 3. Proton exchange membrane 4. Cathode catalyst layer 4' Anode catalyst layer 5...Cathode 5' Anode 11. Proton conductor 12. Catalyst particles 21 Proton conductor 22. Catalytic particles e1: Thickness of the cathode layer e2: Thickness of the anode layer
Claims
1. 1. A proton exchange membrane for a fuel cell, said membrane comprising an anode surface on an anode side and a cathode surface on a cathode side, said membrane comprising two layers: Cathode surface, SO 3 a self-regenerating conductive cathode layer comprising at least one polymer (iii) having H groups; and SO, which brings the anode surface 3 a conductive anode layer comprising at least one polymer (iii') having H groups; Including, said polymers (iii) and (iii') may be the same or different; The membrane is a proton exchange membrane, characterized in that the cathode layer comprises at least one polymer (i) carrying a thiol group (-SH).
2. 2. The proton exchange membrane of claim 1, wherein the cathode layer and / or the anode layer further comprise an inorganic polymer (ii) and / or (ii'), respectively, wherein the polymers (ii) and (ii') may be the same or different.
3. 3. The proton exchange membrane according to claim 1, wherein the polymer (i) having an SH group is (3-mercaptopropyl)trimethoxysilane (MPTMS).
4. 4. Proton exchange membrane according to claim 1, wherein the polymer (ii) and / or (ii') is TEOS (tetraethyl orthosilicate) or TMOS (tetramethyl orthosilicate).
5. 5. The proton exchange membrane according to claim 1, wherein the polymer (iii) and / or (iii') is CSPTC (2-(4-chlorosulfonylphenyl)ethyltrichlorosilane).
6. In the cathode layer, the SO concentration relative to the SH group concentration 3 6. Proton exchange membrane according to claim 1, wherein the ratio of H-group concentrations is between 0.5 and 4, preferably between 1 and 4.
7. 7. The proton exchange membrane according to claim 1, wherein the cathode layer has a thickness of between 3 and 15 μm, in particular between 5 and 10 μm, preferably between 5 and 7 μm.
8. 8. The proton exchange membrane according to claim 1, wherein the cathode layer exhibits an increasing SH group concentration gradient from its inner surface with the anode layer towards its outer surface, providing an interface with a cathode catalyst layer.
9. In the cathode layer, the polymers (ii), (iii) and (i) are in a ratio of 1:2:1; In the anode layer, the polymers (ii') and (iii') are in a ratio of 1:2; A proton exchange membrane according to any one of claims 1 to 8.
10. 10. The fuel cell according to any one of claims 1 to 9, comprising a bilayer membrane, the bilayer membrane being coated with a cathode catalyst layer on an outer surface of the cathode layer and with an anode catalyst layer on an outer surface of the anode layer.
11. 11. The fuel cell of claim 10, wherein the cathode catalyst layer comprises the polymers (i) and (iii) and the anode catalyst layer comprises the polymer (iii').
12. a polymer (i) having at least one thiol group (-SH) and at least one SO 3 forming fibers constituting a cathode layer from a solution containing a polymer (iii) having an H group by electrospinning; - at least one SO 3 forming fibers constituting the anode layer by electrospinning from a solution containing a polymer (iii') having an H group; - forming an anode layer and a cathode layer, respectively, from the obtained fibers; - attaching the cathode layer to the anode layer; A method for producing the proton exchange membrane according to claim 1 , comprising:
Citation Information
Patent Citations
Electrospun nanofiber WEBS for membrane reinforcement in fuel cells
CA2950775A1
High-temperature durable polymetric solid electrolyte membrane
JP2006059552A
Manufacturing method of proton conductive material
JP2006120560A
Perfluoro polyether rubber composition for polymer electrolyte film and ion-conductive polymer electrolyte film
JP2008115236A
Proton conductive material, membrane-electrode binder, proton conductive film, proton conductive film with bond layer, membrane-electrode assembly, and polymer electrolyte fuel cell
JP2009099564A